Process of Resolving Cases of Traffic Violations which Resulted Death - Hendri Listiawan Nugroho; Achmad Sulchan (Law Development Journal, 2020)
A traffic violation is an act that is contrary to traffic and/or its implementing regulations, which may or may not cause loss of life or property as well as security, order and smoothness of traffic (kamtibcarlantas). This writing aims to identify and analyze the process of resolving cases of traffic violations that cause people to die based on, constraints, and solutions in solving cases. The approach method used is a sociological juridical approach. The research specification used is descriptive analysis, primary and secondary data sources and uses qualitative analysis. This writing is analyzed with the theory of justice and the theory of legal certainty to answer the problem. The process of settlement of cases is carried out in accordance with the criminal procedure law as regulated in the Criminal Procedure Code (KUHAP), starting from investigations, investigations, prosecution by the Public Prosecutor, and trials in court where criminal decisions are subsequently sentenced to the perpetrators. The obstacles faced include: inadequate infrastructure, lack of human resources, lack of coordination between the police and prosecutors, lack of public legal awareness, and lack of compliance with legal rules by the community. The solutions applied were in the form of: completing the facilities and infrastructure, improving the quality of human resources, improving coordination between the police and prosecutors, holding outreach to the public.